Dinamika Interaksi Sosial di Lorong-Lorong Kota Makassar di Gowa: Studi Etnografi di Era Perubahan Modernisasi - Alfira Alfira; Hafsya Wulandari A.; Haniah Haniah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Dynamics of social interaction within the alleyways of urban neighborhoods, which serve as unique social spaces amid the ongoing processes of modernization. Conducted in the alleyways of Makassar City, this research employs an ethnographic approach through participant observation, in-depth interviews, and field note documentation. The findings reveal that alleyways function not only as physical pathways but also as vibrant social arenas where communal activities—such as neighborhood gatherings, mutual aid, and small-scale household economies—take place. Modernization introduces significant changes to these patterns of interaction. On one hand, infrastructural development, technological penetration, and increased mobility foster new forms of interaction that are more practical and individualistic. On the other hand, core values of solidarity, including mutual support and close neighborly relations, continue to persist through community-based initiatives, local empowerment programs, and informal shared activities. The study concludes that alleyways represent hybrid social spaces where tradition and modernity intersect, demonstrating residents’ efforts to maintain social cohesion despite the pressures of social change. These findings are expected to contribute to policy development and inform local authorities in designing culturally sensitive alleyway development programs.